1990
DOI: 10.1002/tcm.1770100205
|View full text |Cite
|
Sign up to set email alerts
|

Tumor promotion: Models and assay systems

Abstract: Tumor promotion is defined operationally from two-stage models of experimental carcinogenesis. It is, therefore, in a strict sense, possible to identify tumor promoters only from such models. The development and use of in vitro two-stage cell transformation assays was a logical extension toward in vitro short-term testing for tumor promoters. Another approach is to apply mechanistic knowledge of the tumor promotion process in developing end points for such assays. In this context, we have been examining the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 78 publications
1
13
0
3
Order By: Relevance
“…The correlation between neoplastic transformation and reduced gap junctional communication (Atkinson et al, 1981;Azarnia and Loewenstein, 1984;de Feijter et al, 1990) has led to the hypothesis that reduced cell-cell communication is a critical step in multistage carcinogenesis (Fitzgerald and Yamasaki, 1990;Trosko et al, 1990). PKC has received considerable attention because PKC activators (e.g.…”
mentioning
confidence: 99%
“…The correlation between neoplastic transformation and reduced gap junctional communication (Atkinson et al, 1981;Azarnia and Loewenstein, 1984;de Feijter et al, 1990) has led to the hypothesis that reduced cell-cell communication is a critical step in multistage carcinogenesis (Fitzgerald and Yamasaki, 1990;Trosko et al, 1990). PKC has received considerable attention because PKC activators (e.g.…”
mentioning
confidence: 99%
“…Em trabalhos prévios, após utilização de protocolo de iniciação da carcinogênese, a atividade de GSTP é signifi cativamente aumentada em fígado de ratos púberes, assim como em adultos, quando comparados com animais controle não submetidos a processo de iniciação (10) . Focos espontâneos aumentam com a idade e são mais visíveis em ratos machos (20) .…”
Section: Methodsunclassified
“…A carcinogênese é um processo dinâmico que envolve os estágios de iniciação, promoção e progressão e nesse processo as alterações gênicas são acompanhadas de modifi cações no fenótipo das células (5,7,8,9,10,21,23) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…• Phenobarbital has been tested in multiple studies of GJIC, and was used as a positive control in rodent cell lines by several different investigators. It has been evaluated in studies using several different measures of GJIC, including dye coupling, electron microscopy, gap junction gene expression, and in vivo assays (Fitzgerald and Yamasaki, 1990). • In vitro studies using phenobarbital in liver cell cultures from multiple species have demonstrated a speciesspecific tumor promoting capability, in that phenobarbital is an effective inhibitor of intracellular gap junction communication in rodent cells, but not in primate or human liver cells (Kamendulis et al, 2002); • Phenobarbital has not been shown to be associated with liver cancer in humans, even after long-term relatively high-dose administration (Whysner et al, 1996) suggesting that a "threshold dose" model applies.…”
Section: Mouse: Liver Tumorsmentioning
confidence: 99%